Smart monitoring information system based on RF 433 Mhz (SMIS) - Ouldzira Hicham; Ahmed Mouhsen; Hajar Lagraini; Abdelmoumen Tabyaoui; Mostafa Chhiba (Institute of Advanced Engineering and Science, 2019)
Many research works are devoted to the design of remote control systems of objects. Remote monitoring is among the technologies of data acquisition on a remote object and its characteristics without physical contact with it. These data can be collected by acoustic waves, the distribution of forces and electromagnetic energy to process them to locate the object and its characteristics. This paper presents a smart monitoring information system based on RF 433MHz, Arduinonano and arduinouno named SMIS.